Interactions between tram passengers and road vehicles at tram stops - a pilot study - Piotr Soczówka; Renata Żochowska (Transactions on Transport Sciences, 2020)
Modern urban and metropolitan areas face numerous problems associated with transport activity, such as pollution, congestion, noise or traffic incidents. One of the solutions to cope with these issues may be encouraging people to use means of public transport instead of private cars. However, that requires the fulfillment of demands that present, as well as potential, passengers have. One of the most important passengers' demands is safety of all operations of public transport. In case of tram transport one aspect of safety is associated with the process of boarding the tram and alighting from it at stops separated from tram tracks by roadway, which forces passengers to enter the road. It is hazardous for all passengers and poses an additional risk for disabled passengers. In this paper an analysis of interactions between tram passengers and drivers of road vehicles at such tram stops, during the boarding and alighting from the tram was performed. For that purpose also a classification of tram stops stations was conducted, with the number of traffic lanes that passengers have to pass through being the main criterion. Also, the review of literature on this subject was conducted. For the research during the pilot study the tram network in Metropolis GZM in southern Poland was chosen and all tram stops stations on the network were inspected in order to obtain characteristics necessary for classification. Research during this pilot study allowed to identify conflict interactions that take place at tram stops. Examples of such interactions have been presented in the paper. Paper also contains conclusions and propositions of changes that may be implemented at tram stops that may lead to increase of the level of safety of passengers who try to board the tram or alight from the tram.